THE AMOUNT OF BALLOON FIXATION FLUID VOLUME EFFECTSS ON URINE LEAKAGE IN PERMANENT CATHETER INSTALLATION - Veronica Ririn marwaningsih (Jurnal Manajemen Asuhan Keperawatan, 2021)
THE AMOUNT OF BALLOON FIXATION FLUID VOLUME EFFECTSS ON URINE LEAKAGE IN PERMANENT CATHETER INSTALLATION Ririn Marwaningsih1, Sunarsih2, NikenAstuti 3 1Program studi D III, Sekolah Tinggi Ilmu Kesehatan Elisabeth Semarang Email : ririn.marwaningsih@yahoo.com 2RS Elisabeth Semarang Email : sunarsihutagalung1@gmail.com ABSTRACT Background: The appropriate volume of balloon fixation still becomes a matter of discussion in the permanent catheter installation. The providing of fixation fluid on varied catheter installation is still found practically. The incidence of urine leakage in patients with permanent catheters is still often found. The amount of fixation fluid volume used needs to be studied to provide input on how much the right fixation volume for the permanent catheter installation. The purpose of this study is to determine the role of the amount of catheter balloon fixation volume on the incidence of permanent catheter leakage. Methods: The design of this research is analytic observational with a cross-sectional approach. The research population was patients in private hospitals in Semarang who had permanent catheters installed. The sample uses total sampling in accordance with the inclusion and exclusion criteria by taking samples from 17-21 January 2019 as many as 53 respondents. Results: 33 (62.3%) respondents had 10 ml fixation volume permanent catheter (62.3%), 13 respondents (24.5%) had permanent 20 ml balloon fixation volume and 7 (13.2%) respondents had permanent 25 ml balloon fixation volume. There were 7 respondents (13.2%) who had urine leakage and 46 respondents (86.8%) did not. The Mann-Whitney test showed a p value of 0.047 (<0.05). Conclusion: the volume of balloon fixation fluid has a role in the incidence of urine leakage in permanent catheter installation. Key words: volume of catheter balloon fixation fluid, catheter balloon, urine leakage, permanent catheter